PEMANFAATAN BEKATUL DAN WAKTU KUKUS YANG BERBEDA TERHADAP ORGANOLEPTIK NUGGET AYAM - Chairil Anwar; Irhami Irhami; Ika Rezvani Aprita (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
Chicken nuggets are one of the fast food that is currently in high demand from parents to children. Chicken nuggets are also food products made from chicken meat that has been grounded. One of the raw materials that can be used for the processing of chicken nuggets is bran flour that is rich in protein.Bran is a byproduct of rice processing or grain formed from the outer layer of rice broken skin in the slide to produce white rice or head rice. One of the processes in making chicken nuggets is steaming. This research was aimed to study the effect of the addition of bran flour and length of steaming on chicken nuggets. The research design used was a Completely Randomized Design (CRD) consisting of 2 treatments. Faktor A was the concentration of bran flour and factor B was length of steaming. From the research, it showed that the treatment of bran flour concentrations had not significant effect on protein, organolepticof color and aroma however it had a significant effect on the texture and taste of nuggets. Length of steaming had not significant effect on protein, organoleptic color, aroma texture, yet significantly effect on organoleptic of taste. The interaction between these treatments had a significant effect on protein but had notsignificant effect on organoleptic color, texture, aroma, and taste of the chicken nuggets produced. The best quality of chicken nuggets was obtained from the treatment of 20% bran flour concentration and20-minute steaming length (A2B1) with product characteristics included protein 13.28%, color 2.76, texture 2.82, aroma 3.01and taste 2.89.